Pengaruh promosi dan persepsi harga terhadap keputusan pembelian wafer Tango di Tara Minimarket Surabaya - Munir, Mishbahul; Aminah, Siti (ARKA INSTITUTE, 2023)
This study aims to see the influence of promotion and price perception as factors in purchasing decisions on Tango wafers at Tara Surabaya Minimarket. The approach used in this study uses a quantitative approach. The population in this study were consumers who had consumed Tango wafers. The sampling method used was the purposive sampling technique with a sample size of 45 respondents. The data used were primary data and secondary data. The data obtained were analyzed using the Partial Least Square (PLS) Technique. Based on the results of the study, it can be seen that promotion and price perception have a positive effect on purchasing decisions on Tango wafers at Tara Surabaya Minimarket. The results of this study indicate that promotion and price perception have a positive effect on purchasing decisions. So it can be concluded that the better the level of promotion, the higher the level of purchasing decisions, the lower the level of promotion, the lower the level of purchasing decisions.